Traditional Music in Coastal Louisiana : The 1934 Lomax Recordings - Caffery, Joshua Clegg (Book collections on Project MUSE., 2013)
Alan Lomax's prolific sixty-four-year career as a folklorist and musicologist began with a trip across the South and into the heart of Louisiana's Cajun country during the height of the Great Depression. In 1934, his father John, then curator of the Library of Congress's Archive of American Folk Song, took an eighteen-year-old Alan and a 300-pound aluminum disk recorder into the rice fields of Jennings, along the waterways of New Iberia, and behind the gates of Angola State Penitentiary to collect vestiges of African American and Acadian musical tradition. These recordings now serve as the.